2015
DOI: 10.1557/jmr.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of grain size on melting temperature of Al nanocrystals by molecular dynamics simulation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…As shown in Figure 1, for the melting process of nanocrystalline gold with a mean grain size of 14 nm, the melting originates from the grain boundaries to the inner grain, similar to the other simulations for Ag and Al. 36 In Figure 2, the localized changes of structures near the melting point are shown by common neighbor analysis, polyhedral template matching, and displacement magnitude matching analysis. From common neighbor analysis, with the increase of temperature, the atoms in the inner grain become active and the structure deviates from fcc.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 1, for the melting process of nanocrystalline gold with a mean grain size of 14 nm, the melting originates from the grain boundaries to the inner grain, similar to the other simulations for Ag and Al. 36 In Figure 2, the localized changes of structures near the melting point are shown by common neighbor analysis, polyhedral template matching, and displacement magnitude matching analysis. From common neighbor analysis, with the increase of temperature, the atoms in the inner grain become active and the structure deviates from fcc.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…34 Noori et al reported that for Al nanocrystals with a grain size of more than 14 nm, the melting point is constant and similar to that of perfect crystals. 36 Results on Cu bicrystals imply that the melting point is connected with types and angles of grain boundaries. 33,37 Here, we explore the process and trends for metal nanocrystal melting by analyzing the melting of nanocrystalline Au with a mean grain size from 1.7 to 23 nm with MD simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperatures from solid to liquid phase transition are about 1670 K and 1540 K for the crystalline and polycrystalline models, respectively. In Noori’s study 26 , the MD simulation was utilized to realize the effect of grain size on the melting temperature of Al nanocrystals. Their results show that the melting temperature becomes lower when the grain size is smaller.…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures from solid to liquid phase transition are about 1670 K and 1540 K for the crystalline and polycrystalline models, respectively. In Noori's study [19], the MD simulation was utilized to realize the effect of grain size on the melting temperature of Al nanocrystals. Their results show that the melting temperature becomes lower when the grain size is smaller.…”
Section: Introductionmentioning
confidence: 99%